Embryo transfer techniques and their impact on the outcome of assisted conception - Coats, E.M. (2017)
This thesis describes the development of a novel system to grade the ‘difficulty’ of an embryo transfer (ET) procedure. A systematic review of the prevalence of ‘difficult’ ET has revealed marked heterogeneity across the literature with no real consensus ‘definition’ or ‘grading system’ available for clinicians to use. A new systematic approach to grading ET procedures has been proposed and tested. It has the ablity to predict IVF outcomes accurately and has proven to be reliable.